STRENGTHENING ACADEMIC READINESS AND CHARACTER OF HIGH SCHOOL STUDENTS IN GARUT REGENCY IN FACING THE TRANSITION TO HIGHER EDUCATION OR THE WORLD OF WORK IN THE DIGITAL ERA - Dahlan, Taufiqulloh; Asep Deni Normansyah; Yuni Indriyani; Cep Miftah Khoerudin; Saiman Rosamsi (Pasundan International of Community Services Journal (PICS-J), 2025)
The digital era requires students to possess both academic readiness and strong character to face the transition to higher education or the world of work. This community service program aimed to strengthen academic readiness and build the character of high school students in Garut Regency, particularly at SMAN 19 Garut. The activities were carried out through socialization, learning motivation training, digital literacy, and soft skills provision on August 14, 2025, by lecturers from the Faculty of Teacher Training and Education, Universitas Pasundan, as part of the Community Service Program (KKN). The results showed an increase in students’ understanding of the importance of digital literacy, academic readiness, and character strengthening such as discipline, responsibility, and work ethic. In conclusion, this program effectively provided students with academic preparation and character development to face the challenges of transitioning to higher education or the workforce. Overall, this community service program proved effective in equipping high school students in Garut Regency with academic readiness and character strengthening. It not only enhanced understanding but also encouraged students to be better prepared for a challenging future. In the future, similar activities should be expanded to other schools so that more students can benefit and be truly ready to face the transition to higher education or the world of work in the digital era.